The Knowledge Need of the College Students on Sexual Health and Their Attitude Towards Sexual Education - Ayşenur Güngör; Gizem Mutlu; Ebru Bulut; Hacer Yalnız Dilcen (Atatürk University, 2024)
Objective: In this study it is aimed to determine the information needs of university students about sexual health and their attitudes towards sexual education.Methods: This study is a descriptive cross-sectional study from quantitative research methods. The research was carried out with the participation of 989 students between September 2021 and January 2022. The data were collected by the researchers using the personal information form, sexual health form, and Attitude towards Sex Education Scale, which were prepared online by the researchers through the Office 365 program. Results: It was determined that the mean age of the students participating in the study was 19.76±1.32 and 77.8% of them were female. It was found that the sociodemographic characteristics of the students, studying in the health department, the place of residence, the education and working status of their parents were found to have a statistically significant effect on their attitudes towards sexual education. Especially, 69.1% of the students wanted to have a sexual health counseling center in the university. It was determined that approximately one fourth of the students related to sexual health received training on this subject, and 58% stated that they wanted to receive training from the health personnel and 15.3% from the counseling center. It has been determined that students need family planning education. It was found statistically significant that students who had knowledge about family planning methods had higher attitudes towards sexual education.Conclusion: It can be suggested to establish advisory boards that students can benefit from in cooperation with universities and health institutions.